Pengaruh Work Life Balance, Efikasi Diri dan Pengalaman Kerja terhadap Komitmen Karyawan: Studi Kasus pada PT Maybank Semarang - Verina Shiva Meifita Sari; Mohammad Fauzan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The objectives of this study are (1) analyze and explain the effect of work life balance on the work commitment of Maybank Semarang employees (2) analyze and explain the effect of self-efficacy on the work commitment of Maybank Semarang employees; (3) analyze and explain the effect of work experience on the work commitment of Maybank Semarang employees. This research is a type of explanatory research. The population of this study was employees of PT Maybank Semarang, as many as 82 employees of Maybank Semarang, and all populations were sampled (census method). The data collection method uses a questionnaire in the form of a google form that is distributed to all respondents. The findings of this study: (1) Work life balance has a positive effect on the commitment of Maybank Semarang employees. This means that the higher the work life balance, the higher the commitment of Maybank Semarang employees; (2) Self-efficacy has a positive effect on the work commitment of Maybank Semarang employees; (3) Work Experience negatively affects the work commitment of Maybank Semarang employees. Based on the findings of this study, it shows that the building of work commitment is influenced by the ability of employees to balance between commitment to work demands and commitment to personal and family interests and self-efficacy, therefore, leaders in policies related to human resource management provide space for employees to build work-life balance and the growth of self-efficacy through the development of employee competencies.